High-Content Screening of Eukaryotic Kinase Inhibitors Identify CHK2 Inhibitor Activity Against Mycobacterium tuberculosis - Shapira, Tirosh; Rankine-Wilson, Leah; Chao, Joseph D.; Pichler, Virginia; Rens, Celine; Pfeifer, Tom; Av-Gay, Yossef (Frontiers in Microbiology, 2020)
A screen of a eukaryotic kinase inhibitor library in an established intracellular infection model identified a set of drug candidates enabling intracellular killing of Mycobacterium tuberculosis (M.tb). M.tb. Screen validity was confirmed by a Z’=0.5, and by detecting previously reported host-targeting anti-M.tb compounds. Inhibitors of the CHK kinase family, specifically CHK2, showed the highest inhibition and lowest toxicity of all kinase families. The screen identified and validated DDUG, a CHK2 inhibitor, as a novel bactericidal anti-M.tb compound. CHK2 inhibition by RNAi phenocopied the intracellular inhibitory effect of DDUG. DDUG was active intracellularly against M.tb, but not other mycobacteria. DDUG also had extracellular activity against M.tb and 3 of 11 bacteria tested. Combined, these observations suggest DDUG acts against M.tb both in the host and in broth. Importantly, DDUG’s validation highlights the screening and analysis methodology developed for this screen, which identified novel anti-M.tb compounds.